Empirical evidence for multidecadal scale global atmospheric electric circuit modulation by the El Niño-Southern Oscillation. (28th December 2022) - Harrison, R Giles; Nicoll, Keri A; Joshi, Manoj; Hawkins, Ed
Abstract: The El Niño-Southern Oscillation (ENSO) modifies precipitation patterns across the planet. Charge separation in disturbed weather and thunderstorms drives the global atmospheric electric circuit (GEC), hence ENSO-induced precipitation changes are anticipated to affect the global circuit. By analysing historical atmospheric electricity data using a new data processing procedure based on the Carnegie curve, signals correlated with ENSO sea surface temperature (SST) anomalies are revealed. These demonstrate a persistent ENSO-GEC relationship for the majority of the twentieth century, in potential gradient data from Lerwick, Shetland and Watheroo, W. Australia. The recovered data is weighted towards the first half of the UTC day, giving a GEC sensitivity up to ∼5% °C −1 of SST anomaly in the Niño 3.4 and 4 regions of the Pacific Ocean. Transferring ENSO variability by electrical means represents an unexplored teleconnection, for example, through proposed GEC effects on stratiform cloud microphysics. The strong ENSO-GEC relationship also provides a quality test for historical atmospheric electricity data, and encourages their use in reducing SST reconstruction uncertainties. Video Abstract: Video Abstract: Empirical evidence for multidecadal scale global atmospheric electric circuit modulation by the El Niño-Southern Oscillation